Kemitraan Pt Astra Agro Lestari Tbk dalam Pilar Astra Hijau di Pasangkayu - Nelsa Nelsa; Intan Fazira; Arifa Nurhidayanti; Yulita Septi Ardaneshwari; Nabilah Sanjana Putri Armasnsyah; Nur Fadhilah Dwi Putri Zaenong; Devi Petonengan; Ammatullah Anisah; Friscia Novianti Setiawan; Qiska Natasyah Chandra; I Gede Aditya Purwanto; Faustino Andresta Soande; Moh. Taqwa; Nawawi Natsir; Muhammad Afandi; Askar Mayusa (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze the implementation of the Astra Hijau program as a form of corporate social responsibility (CSR) by PT Astra Agro Lestari Tbk through PT Pasangkayu, as well as the partnership models that support sustainable development in Pasangkayu Regency. Using a qualitative descriptive approach, the research findings indicate that Astra Hijau has successfully increased public awareness and participation in environmental conservation through programs such as clean water assistance, waste bank revitalization, reforestation, Ecobrick initiatives, and the empowerment of environmental cadres. The program’s success is supported by collaborative partnerships between companies, the government, schools, communities, the media, women, and youth. This program is considered capable of delivering integrated social, economic, and environmental impacts while improving the quality of life for the community.